Exploring the Impact of Ethnocentrism, and Country of Origin on Consumer Purchase Intentions: A Case Jingdezhen Blue-and-White Ceramics - Yifeng, Fang; Yaacob, Husaini Bin (South Asian Journal of Social Sciences and Humanities, 2024)
In China, the native people living in the society have great enthusiasm for their country and they  always prefer using and consuming their homeland-manufactured products. Moreover, Chinese  have their own culture in which they possess different arts and creative commodities  consumption and purchasing to follow their traditional norms. This study investigates the  patriotic nature of Chinese customers, who have a strong preference for their home-made  products and cultural heritage. The research uses an empirical model to examine the relationship  between animosity, ethnocentrism, country of origin, and country knowledge, as well as  perceived warmth as a mediator. The study used a positivist philosophy with a deductive  approach, using the S-O-R theory as the empirical support. Quantitative primary data was  collected from 280 customers of blue and white ceramic products, with a total sample size of  280. The SEM technique revealed that country of origin and ethnocentrism significantly  influences customer purchase intentions for ceramic products. Furthermore, the mediation  analysis revealed that customer ethnocentrism indirectly impacts purchase intentions through  perceived warmth. The study concludes that Chinese customers have a high devotion to their  mother country's products, and the behavior of native sellers and general society people is crucial  in stimulating their purchase intentions.
Keywords: ethnocentrism; customer animosity; perceived warmth; SOR theory; ceramic products; Chinese population